Perceptions of accounting academicians toward the issue of information technology integration into the accounting curriculum - Ismail, Noor Azizi; Salim, Basariah (Kementerian Pendidikan Malaysia, 2005)
This study sought to investigate the perceptions of accounting academicians toward the issue of Information Technology (IT)integration into the accounting curriculum in the specific context of Malaysian Higher Learning Institutions. Data from 76 accounting academicians was collected using a mail questionnaire.The results indicated that most accounting academicians are satisfied with the hardware facilities, support and appreciation received from their head of department and colleagues. Many of them recognized the importance of IT knowledge and skills in enhancing the future of the accounting profession. However, they also showed their dissatisfaction on several technical aspects such as adequacy of application software, network services, technical supports, and allocation of IT-related training. Furthermore, whilst a majority of accounting academicians felt that IT should be integrated into all major areas of accounting, many of them felt that the extent of IT knowledge and skills being integrated into the accounting curriculum is insufficient.